(untitled) (Universal International Scientific Journal, 2026)
This article examines the concepts of research and research competence, clarifying their definitions, core characteristics, and professional significance. Drawing on a synthesis of contemporary scholarly literature, the paper analyzes how research is conceptualized as a systematic, rigorous, and purposeful process aimed at generating reliable knowledge and solving problems. It further explores research competence as a multidimensional construct integrating knowledge, cognitive abilities, practical skills, motivation, and personal attributes necessary for effective research practice. The review identifies strong consensus across studies regarding the integrative nature of research competence, despite variations in structural frameworks and component classifications. Additionally, the article highlights the educational and professional benefits of developing research competence, including enhanced critical thinking, communication skills, motivation, academic achievement, and career readiness. Particular attention is given to its importance in graduate and postgraduate education as a foundation for evidence-based practice and innovation. The findings confirm that fostering research competence is essential for quality education, professional excellence, and sustainable knowledge-based development.